Adsorpsi Ion Logam Cr (VI) dari Adsorben Karbon Aktif Tongkol Jagung (Zea Mays) - Khalisa Khalisa; Fahilatul Syukro; Nuzulia Yona; Putri Nugraha; Edi Nasra; Desy Kurniawati (Jurnal Pendidikan Kimia, Fisika dan Biologi, 2025)
The use of Cr (Chromium) in industry and daily life produces toxic waste harmful to humans and the environment. This study aims to evaluate the effectiveness of activated carbon from corn cobs as an adsorbent for Cr(VI) heavy metal. Corn cobs, which contain 40–44% cellulose, were carbonized at 500°C using 6% sodium carbonate and characterized with an IR spectrophotometer. Adsorption tests were conducted by varying pH and contact time to determine optimal conditions. FTIR results revealed functional groups such as C≡C stretch, C=C=C stretch, and C–O bend. After activation, O–H groups appeared, indicating the presence of aromatic compounds, which are typical in activated carbon. The optimum pH for Cr(VI) adsorption was pH 4, with an adsorption rate of 65.35%. The optimum contact time was 60 minutes, resulting in 3.2% Cr(VI) adsorbed and a maximum adsorption capacity of 0.089 mg/g. In conclusion, corn cobs are a promising, eco-friendly, and effective natural material for adsorbing Cr(VI) heavy metal ions.